Immersive Invaders: Privacy Threats from Deceptive Design in Virtual Reality Games and Applications - Hadan, Hilda; Valiquette, Michaela; Lennart, Nacke; Zhang-Kennedy, Leah (Association for Computing Machinery, 2025)
Virtual Reality (VR) technologies offer immersive experiences but collect substantial user data. While deceptive design is well-studied in 2D platforms, little is known about its manifestation in VR environments and its impact on user privacy. This research investigates deceptive designs in privacy communication and interaction mechanisms of 12 top-rated VR games and applications through autoethnographic evaluation of the applications and thematic analysis of privacy policies. We found that while many deceptive designs rely on 2D interfaces, some VR-unique features, while not directly enabling deception, amplified data disclosure behaviors, and obscured actual data practices. Convoluted privacy policies and manipulative consent practices further hinder comprehension and increase privacy risks. We also observed privacy-preserving design strategies and protective considerations in VR privacy policies. We offer recommendations for ethical VR design that balance immersive experiences with strong privacy protections, guiding researchers, designers, and policymakers to improve privacy in VR environments.